The Influence of Financial Performance on Stock Prices: Analysis of Banking Companies on the Indonesia Stock Exchange in 2020 – 2023 - Jessica Dewi Felicia; Anak Agung Gde Satia Utama (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The economic progress of a country is highly dependent on the condition of its banking system, which plays a vital role in determining the direction of the country's economy. Stock prices serve as a reflection of a company's underlying value and financial health, providing a dynamic indicator of its market value. A company's financial performance encompasses a number of aspects, including operational efficiency and adherence to strategic objectives, which affect stock prices and investor confidence. Financial ratio analysis is an important instrument for investors to understand a company's financial health and performance, and to make informed investment decisions. This research method relies on secondary data from publicly accessible Annual Financial Reports, but researchers must consider the limitations of secondary data compared to primary data to ensure the reliability and suitability of the data. Regression analysis shows that the Earnings per Share (EPS) variable has a positive and statistically significant effect on stock prices, indicating the importance of earnings per share in determining the movement of a company's stock price. The Return on Asset (ROA) and Return on Equity (ROE) variables do not show a significant effect on stock prices, indicating that efficiency in managing a company's assets and equity does not directly affect stock prices. The results of the analysis emphasize the importance of considering various factors, including EPS, ROA, and ROE, as well as external factors such as market and industry conditions, in evaluating a company's stock price for better investment decision-making.